The Effect of Recruitment, Motivation and Work Discipline on Employee Performance at PT Duta Cahaya Putra Medan - Putri, Annisa; Anwar, Yohny (Journal of Community Research and Service, 2024)
This study aims to test and find out more clearly how the influence of recruitment, motivation and work discipline on employee performance at PT Duta Cahaya Putra Medan. This study uses a quantitative method involving 43 respondents. Data collection was carried out using questionnaire distribution. The data obtained was analyzed using a statistical formula, namely by using multiple regression analysis which was managed with the SPSS Version 23 program. The results of the study show that recruitment partially has a negative and insignificant effect on employee performance. The results of the study show that motivation partially has a positive and significant effect on employee performance. The results of the study show that work discipline partially has a positive and significant effect on employee performance. Recruitment, motivation and work discipline simultaneously have a positive and significant effect. 55.6% of employee performance can be explained and obtained from recruitment, motivation and work discipline while the remaining 44.4% is by other factors. Employee performance has a strong relationship with recruitment, motivation and work discipline.